2020
DOI: 10.1039/c9en01112a
|View full text |Cite
|
Sign up to set email alerts
|

Testing the bioaccumulation of manufactured nanomaterials in the freshwater bivalveCorbicula flumineausing a new test method

Abstract: Increasing amounts of manufactured nanomaterials (MNMs) are produced for their industrial use and released to the environment by the usage or disposal of the products. As depending on their annual production rate, substances are subjected to PBT assessment, the availability of reliable methods to evaluate these endpoints for (corresponding) nanoforms/MNMs becomes relevant. The classical method to elucidate the bioaccumulation potential of chemicals has been the flow-through study with fish, which has limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
34
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 79 publications
10
34
1
1
Order By: Relevance
“…accordance with previous observations of Wegner et al (2012) with blue mussels exposed to nanostructural polystyrene (Wegner et al, 2012) and Kuehr, Meisterjahn, et al (2020) with C. fluminea exposed to TiO 2 nanoparticles and to gold nanoparticles (AuNPs). Also in these studies an increased filtration activity and release of feces or pseudo feces were observed (S. Kuehr, Meisterjahn, et al, 2020;Wegner et al, 2012).…”
Section: Accepted Articlesupporting
confidence: 92%
“…accordance with previous observations of Wegner et al (2012) with blue mussels exposed to nanostructural polystyrene (Wegner et al, 2012) and Kuehr, Meisterjahn, et al (2020) with C. fluminea exposed to TiO 2 nanoparticles and to gold nanoparticles (AuNPs). Also in these studies an increased filtration activity and release of feces or pseudo feces were observed (S. Kuehr, Meisterjahn, et al, 2020;Wegner et al, 2012).…”
Section: Accepted Articlesupporting
confidence: 92%
“…Similarly, Kuehr et al [46] observed an enrichment of suspended TiO 2 NPs in the freshwater bivalve C. fluminea with an accumulation factor of more than 9000 that was followed by a complete elimination of the TiO 2 load within 24 h of depuration. This was explained by the rapid and effective release of F/pF containing the previously enriched TiO 2 NPs [46]. Therefore, filter feeding bivalves may play an important role in the exposure of benthic species that feed on the F/pF as described above.…”
Section: Introductionmentioning
confidence: 75%
“…Although the released F/pF were not analyzed for the nPS content, it is likely that the suspended nPS were ingested, concentrated, and finally eliminated by the release of F/pF. Similarly, Kuehr et al [46] observed an enrichment of suspended TiO 2 NPs in the freshwater bivalve C. fluminea with an accumulation factor of more than 9000 that was followed by a complete elimination of the TiO 2 load within 24 h of depuration. This was explained by the rapid and effective release of F/pF containing the previously enriched TiO 2 NPs [46].…”
Section: Introductionmentioning
confidence: 99%
“…47 The bioaccumulation potential of TiO 2 NPs and SWCNTs was also assessed in a sediment dwelling marine polychaete using ICP-OES. 48 More recently the technique of single particle ICP-MS (spICP-MS) has being used, in addition to total metal concentrations measurements of Ag NPs and TiO 2 NPs, to determine particle concentration during metal uptake and elimination from a freshwater bivalve, 49 and from an amphipod, Hyalella azteca. 50 The methods used in these available data sets on aquatic invertebrates might require further validation to enable a standardised protocol for the tissue detection of MNs in a technical guidance document.…”
Section: Using Invertebrate Bioaccumulation Tests As An Alternative To Fish (Tier 2)mentioning
confidence: 99%